Language Interference in Arabic Learning: A Case Study of Islamic Boarding Schools in Indonesia - Muhamad Solehudin; Yusuf Arisandi (Universitas Islam Negeri Palangka Raya, 2024)
This study investigates the phenomenon of language interference in Arabic learning at Darullughah Wadda'dawah (DALWA) Islamic Boarding School in Bangil, Pasuruan. It focuses on identifying the forms of interference, analyzing their impact on students' Arabic language proficiency, and developing strategies to mitigate these challenges. While Arabic language interference has been extensively studied in educational contexts, there is a lack of specific research within Islamic boarding schools (pondok pesantren), particularly those with a diverse student population. Employing a qualitative approach with a case study design, this research utilized semi-structured interviews, classroom observations, and document analysis. Findings reveal that language interference manifests at the phonological, morphological, and syntactic levels, significantly affecting students' confidence and performance in Arabic. Common interference patterns include mispronunciation of Arabic phonemes absent in students' native languages, the use of Indonesian-influenced sentence structures, and inappropriate vocabulary choices. Proposed strategies for mitigation include enhanced phonetic instruction, a contextual approach to vocabulary teaching, and fostering an immersive Arabic-speaking environment. This research contributes to a deeper understanding of language interference dynamics in the context of Islamic education in Indonesia and underscores the need for teaching methods that address these challenges effectively.